Hidradenitis Suppurativa Area and Severity Index Revised (HASI‐R): psychometric property assessment*. (1st May 2021) - Goldfarb, N.; Lowes, M. A.; Butt, M.; King, T.; Alavi, A.; Kirby, J. S.
Summary: Background: Validated, reliable, globally accepted outcome measurement instruments for hidradenitis suppurativa (HS) are needed. Current tools to measure the physical signs domain for HS rely on lesion counts, which are time‐consuming and unreliable. Objectives: To assess the reliability and validity of the Hidradenitis suppurativa Area and Severity Index Revised (HASI‐R) tool, a novel method for assessing HS severity, incorporating signs of inflammation and body surface area involved. Methods: The measurement properties of the HASI‐R tool were evaluated. The tool was created by combining the previously published HASI and Severity and Area Score for Hidradenitis instruments. Twenty raters evaluated 15 patients with HS in a hospital‐based ambulatory dermatology clinic. The objectives of the study were to assess inter‐ and intra‐rater reliability of the HASI‐R and its components, as well as its construct and known‐groups validity. Existing lesion count‐based clinician‐reported measures of HS and their components were also assessed. Raters were also asked their preferences regarding the various HS severity assessment tools. Results: The HASI‐R had moderate inter‐rater reliability [intra‐class correlation coefficients (ICC) 0·60]. This was better than all other HS physical sign outcome measures evaluated, which had poor inter‐rater reliability (ICC < 0·5). HASI‐R had the highest intra‐rater reliability (ICC 0·91). The HASI‐R had good construct validity and demonstrated known‐groups validity. The HASI‐R was also the most preferred tool by all raters. Conclusions: Results from the clinometric assessment of the HASI‐R are encouraging, and support continued evaluation of this clinician‐reported outcome measure.